Multicenter urethroplasty outcomes for urethral stricture disease for patients with neurogenic bladder or bladder dysfunction requiring clean intermittent catheterization (2021)
Background: Our objective is to better comprehend treatment considerations for urethral stricture disease (USD) in patients requiring long-term clean intermittent catheterization (CIC). Patient characteristics, surgical outcomes and complications are unknown in this population. Methods: Six members of the Trauma and Urologic Reconstruction Network of Surgeons (TURNS) participated in a prospective (2009 to present) and retrospective (prior to 2009) database recording patient demographics, surgical approach and outcomes. We included all patients undergoing urethroplasty who perform CIC. Descriptive statistics were used to analyze results. Results: A total of 37 patients with 39 strictures were included. Bladder dysfunction was characterized as detrusor failure in 35% and neurogenic etiology in 65%. Median stricture length was 3 cm (IQR: 1.5–5.5) with 28% repaired with dorsal onlay buccal mucosal graft, 26% excision and primary anastomosis, 8% dorsal inlay, 8% ventral and dorsal, 8% flap based 8% non-transecting and 15% other. Functional success was 90%: 4 patients required DVIU or dilation due to recurrence, with 2 of those ultimately requiring repeat urethroplasty. 86% of patients returned to CIC; no patients reported new pad use for urinary leakage after urethroplasty. During a median follow-up period of 3.1 years (IQR: 1.0–5.3), no patients underwent urinary diversion.